Women, assets, and formal savings: A comparative analysis of Ecuador, Ghana and India. (17th October 2019) - Doss, Cheryl; Swaminathan, Hema; Deere, Carmen Diana; Suchitra, J. Y.; Oduro, Abena D.; Anglade, Boaz
Abstract: Motivation: Savings are an important but often overlooked component of financial inclusion. While women are less active than men in the formal financial sector there is little understanding about their ability to accumulate savings. Purpose: We hypothesize that a woman's individual economic status, measured by her property ownership, is an important driver of her ability to save. Approach and Methods: Women are considered as savers in the formal sector only if they have savings above a minimum threshold. Three measures of women's asset ownership are used: two capture their absolute property status and one their relative status in the household. The data are obtained from three large‐scale surveys that collected individual‐level asset data in Ecuador, Ghana and the Indian state of Karnataka. Logistic regression models are employed to examine the relationship between women's property ownership and accumulation of savings. Findings: The absolute value of a woman's physical assets and her share of household physical wealth are correlated with being able to accumulate formal savings. Women's relative wealth status is more strongly related to their savings, along with education, paid employment and group membership. Conclusions: Women's intrahousehold status, defined by their relative wealth, is critical to determining their ability to save in formal accounts. Policy Implications: Interventions that boost women's bargaining power, by increasing their property ownership, should be encouraged, along with greater efforts to improve girls' access to quality education. Functional literacy training for older women can both reduce barriers to accessing financial institutions and create awareness of their benefits. Constraints to women's participation in the labour force should be removed in tandem with interventions to reduce gender earnings gaps.